KINERJA DINAS TENAGA KERJA DAN ENERGI SUMBER DAYA MINERAL (ESDM) PROVINSI BALI DALAM MELAKUKAN PENGAWASAN TERHADAP TENAGA KERJA ASING - Widya Purnamasari, Ni Putu Pande; Yasintha, Putu Nomy; Prabawati, Ni Putu Anik (CITIZEN CHARTER, 2019)
ABSTRACT Foreign Workers in Bali is increasing every year and there are still widespread foreign workers who do not have work permits (illegal), therefore optimal supervision is needed to prevent violations committed by the foreign workers. Aim of this study to discover performance of the Department of Manpower and Einergy and Miineral Resources of Bali monitoring foreign workers. This used qualitative-descriptive method. Based on resuilts, the performance Department in monitoring foreign workers had gone well but was not optimal because there were still obstacles including lack of human resources and infrastructure, very narrow supervision targets, and lack of coaching which is carried out mainly towards small companies. Keyword: Performance, Supervising, Foreign Workers.